Pesantren and the preservation of traditional religious authority in the digital age - Dodik Harnadi; Hotman Siahaan; Masdar Hilmy (Masyarakat, Kebudayaan dan Politik, 2021)
Kiai is the Javanese term of ulama in the traditional Muslim community. It generally refers to a person who has a deep understanding of Islam and leads the institution of traditional Islamic education called pondok pesantren or Islamic boarding school. Indeed, the strength of a Kiai is based on his leadership at the pesantren that has functioned as a space for cultural-social reproduction. While the attention of many researchers focused on the shifting of Islamic authority in the digital age, not much of them paid special attention to the survival of Kiai’s authority. This study aims to examine the role of pesantren in preserving the authority of the Kiai in the digital age. This study employed qualitative method and utilized the cultural reproduction theory of Pierre Bourdieu. This study found that Kiai’s authority continues to survive because pesantren functioned as a space for transmitting cultural values, including the recognition of Kiai’s high position. As a social and cultural reproduction space, pesantren becomes a field that forms habitus through the transmission of its cultural values which is naturally formed in the daily practices of the santri.